EFFECTIVENESS OF SOURSOP LEAF EXTRACT (Annona muricata L.) ON THE MORTALITY OF GRAYCOOL CATERPRISES (Spodoptera litura) - Salessy, Sitti; Awan, Ali; Wael, Syahran (RUMPHIUS, 2022)
Annona muricata extract with a concentration of 20% during the day showed an average value of 29%, the afternoon 1:14%, whereas 40% at a concentration of 29% the morning, during the day 86%, and afternoon 1.14%. Concentration of 60% and 1.14% morning, afternoon and evening 1.43% 1.14%. Results of Kruskal-Wallis statistics on mortality of Spodoptera litura showed a significant difference between the P values ​​indicated by early spraying time (0.317), noon (0.254), and late (1,000). With treatment A.muricata extract statistical results Kruskal-Wallis P value <0.05. A.muricata extract treatment given to the mustard plant as much as 10 ml each spraying. Based on the observation and analysis of the data it can be concluded that the extract of A. muricata at a concentration of 20%, 40%, and 60% can affect the mortality of Spodoptera litura.